Análisis de mecanismos de participación local en Colombia : Audiencias de Rendición de Cuentas y Consejos Territoriales de Planeación. (2017)
This article aims to analyze the design and implementation of two institutional mechanisms to promote citizen participation at the local level in Colombia: Audiences for Accountability and Territorial Planning Councils (CTP). After the analysis, which involves a comparative study of its implementation in two Colombian municipalities, deficiencies in the institutional design of these mechanisms are identified, implying the need to rethink and reformulate these tools in the search to consolidate citizen participation and to improve government actions in the local Colombian sphere.